Calculating Resistance of Container Ship with Specific Turning Angle using Form Factor Coefficient K - Hoang, Cong Liem; Pham, Van Sang; Le, Thanh Tung (Old Journal, 2020)
In stability and control of ship, knowledge about ship resistance is very important. In order to control a ship – especially when she changes the course- it is necessary to obtain the resistance value at specific turning angles. In reality, results of ship resistance obtained from doing experiments or simulations using small models have to be adjusted to get the resistance of real ships. This will be more complicated if the ship does not go straight. In this research, the authors try to solve this problem by using form factor k. All the results were obtained using a 170 m long container ship.